Integrating welfare economics in social work curriculum: a Malaysian case. Issue 5 (4th July 2018) - Jafar, Muhammad; Hatta, Zulkarnain A.; Nikku, Bala Raju
ABSTRACT: This paper makes a case for why welfare economics should be integrated and taught in social work courses, taking Malaysia a case in point. This is mainly a conceptual paper and secondary data are used to further support the arguments. Commencement of professional social work in Malaysia dates to 1946, to address the socio-economic problems of the Malaysians and migrants at that time. Social workers need a multi-pronged approach that is crucial to address the human problems that includes psychological, social, political, cultural and economic at micro and macro levels. Most of the problems referred to the social workers stem from poverty, unemployment, low access to material resources and corrupt governance practices coupled with unjust economic policies. Keeping in view the diverse economic needs and strengths of the clients referred to social workers, it is necessary that social workers are equipped with appropriate skills that include broader understanding about political economy. This paper argued that integration of welfare economics in the social work curricula is an urgent need considering the Malaysian economic development, austerity measures and the proactive role that social work as a human rights profession could play in the Malaysian society.